Determinan Keputusan Mahasiswa Muslim dalam Memilih Melanjutkan ke IAIN Pekalongan - Wijoyanto, Yusuf; Mas’ud, Fuad (Program Pascasarjana STIE Amkop Makassar, 2021)
Abstract This study aims to obtain empirical evidence and analyze theory of planned behavior, religiosity and Image against intention. Theory of planned behavior consists of several variables which include: behavioral beliefs, normative beliefs, control beliefs, attitudes towards behavior, subjective norms, perceived behavior control and intentions.The population in this study were Muslim students who continued their studies at IAIN Pekalongan. The total sample used in this study was 182 students based on predetermined criteria. Data analysis was performed using Structural Equation Modeling (SEM). The results of the analysis of this study indicate that all variables used in this study have a positive and significant effect. Behavioral beliefs and religiosity have a positive and significant effect on student attitudes in choosing to continue their studies in Pekalongan, normative beliefs have a positive and significant effect on subjective norms, belief control has a positive and significant effect on perceived behavioral con trol. Then the attitude variables, subjective norms, perceived behavioral control, religiosity and image have a positive and significant effect on the intention of students to continue their studies at IAIN Pekalongan. Keywords: Intention,religiosity, image and theory of planned behavior